Pop Up Ads Affecting Buying Decision Mediated by Purchase Intention in Online Marketplace (Lazada) in Denpasar - Vincent Wijaya; Ni Made Dhian Rani Yulianti (TIERS Information Technology Journal, 2020)
This study aims to determine the effect of pop up ads toward buying decision with purchase intention as the mediating variable. Pop up ads is a form of digital marketing, where pops up when someone open a website. Denpasar known as the capital city of Bali, and known for the the highest rate of education in Bali.The respondence of this research is 150 people who live in Denpasar, accustomed to using internet, and have seen Lazada’s pop up ads. Pop up ads have a negative effect toward purchase intention, and buying behaviour, while purchase intention have a positive effect toward buying decision